Crusading and archaeology - Shotten-Hallel, Vardit 1971-; Weetch, Rosie (Routledge, 2021)
This collection of thirteen original essays by leading archaeologists and historians - as well as by specialists on material culture - amounts to the first collection of articles for some time to focus on the contributions of archaeology to the study of the Crusades. The Crusades here are defined in the widest possible sense as the book covers the Latin East, western Europe and the Baltic region.
Keywords: Funde; Archäologie; Kreuzzüge; Ausgrabung; Kreuzfahrerstaaten; Konferenzschrift -- 2016 -- Odense